Dinamika Sosial dan Keberlanjutan Tradisi Batamat Al-Qur'an dalam Masyarakat Banjar Kontemporer - Ainah, Noor; Syamsuni (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
Batamat Qur'an is a tradition that is deeply rooted in the soul of the Banjar people; in its development, it also experiences friction with social, economic, political, and even technological factors. This paper explains the variety, dynamics, and sustainability of this tradition in Tanah Banjar. By using Blumer's symbolic interactionism, some of the essential findings of this study are as follows. In terms of purpose, batamat is divided into batamat kanakan, batamat Pangtin, batamat maniga hari, batamat tadarusan, and batamat for certain purposes such as business blessings or part of a test. Meanwhile, in terms of excitement, the model of batamat is divided into traditional Banjarese one, TPA/TPQ style, ordinary, and online. The various traditions of the Banjarese batamat explain the social, economic, and political dynamics of the Banjar people. The different offerings, attributes, meanings, and functions of the batamat itself reflect the personality of the agrarian Banjar community that puts forward Islamic values ​​that are understood traditionally, even to the point of taking root in the world of politics. While continuing this tradition amid the information technology era, it seems that it can still survive with some critical notes. The urgency of maintaining the batamat practice is undoubtedly a big question in the Banjar community as the leading actor in the tradition. Moreover, other models of khatam al-Quran are familiar in Banjar society, along with the increasingly diverse models of teaching the Koran that continue to emerge